2021
DOI: 10.11606/s1518-8787.2021055003152
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with stress, anxiety, and depression during social distancing in Brazil

Abstract: OBJECTIVE: To estimate the prevalence of clinical signs and symptoms of severe/extreme stress, anxiety, and depression, as well as their associated factors, among Brazilians during social distancing. METHODS: This is a cross-sectional study conducted in April/May 2020 with 3,200 Brazilians over 18 years old. Respondents’ sociodemographic and clinical data were collected using an online questionnaire, which also included the 21-item Depression, Anxiety and Stress Scale (DASS-21) to assess emotional symptoms. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 37 publications
4
36
2
8
Order By: Relevance
“…The results indicate that the majority of undergraduates surveyed presented mild to severe symptoms of depression (60.5%), anxiety (52.5%) and stress (57.5%). Compared with other studies during the COVID-19 pandemic, using the same instrument, the percentages of the present study were higher than those found in the Brazilian adult population for depression (21.5%, 46.4% and 54.5%), anxiety (19.4%, 39.7% and 41.1%) and stress (21.5%, 42.2% and 45.7%) [ 7 , 9 , 10 ], and in the population of 8 countries (China, Spain, Italy, Iran, USA, Turkey, Nepal, Denmark) for depression (14.6% to 48.3%) and anxiety (6.3% to 50.9%) [ 5 ].…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…The results indicate that the majority of undergraduates surveyed presented mild to severe symptoms of depression (60.5%), anxiety (52.5%) and stress (57.5%). Compared with other studies during the COVID-19 pandemic, using the same instrument, the percentages of the present study were higher than those found in the Brazilian adult population for depression (21.5%, 46.4% and 54.5%), anxiety (19.4%, 39.7% and 41.1%) and stress (21.5%, 42.2% and 45.7%) [ 7 , 9 , 10 ], and in the population of 8 countries (China, Spain, Italy, Iran, USA, Turkey, Nepal, Denmark) for depression (14.6% to 48.3%) and anxiety (6.3% to 50.9%) [ 5 ].…”
Section: Discussioncontrasting
confidence: 91%
“…During the period of data collection, most respondents had restarted academic activities remotely (79.8%) about 1 or 2 months ago (August 17, 2020), after the interruption of the school year. Thus, the high prevalence of depression, anxiety and stress symptoms also suggests the additional psychological impact of the pandemic on students due to repercussions on education, such as adaptation to remote classes, as assessed in other studies [ 10 , 15 , 16 , 25 ].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations